TanDEM-X PolarDEM 90 m of Antarctica: Generation and error characterization - Wessel, Birgit; Huber, Martin; Wohlfart, Christian; Bertram, Adina; Osterkamp, Nicole; Marschalk, Ursula; Gruber, Astrid; Reuß, Felix; Abdullahi, Sahra; Georg, Isabel; Roth, Achim (The Cryosphere, 2021)
We present the generation and validation of an updated version of the TanDEM-X Digital Elevation Model (DEM) of Antarctica: the TanDEM-X PolarDEM 90 m of Antarctica. Improvements compared to the global TanDEM-X DEM version include filling of gaps with newer acquisitions, interpolating of smaller voids, smoothing of noisy areas and replacing frozen or open sea areas with geoid undulations. For the latter, a new semi-automatic editing approach allowed the delineation of the coastline from DEM and amplitude data. Finally, the DEM was transformed into the cartographic Antarctic Polar Stereographic projection with a homogeneous metric spacing in northing and easting of 90 meters. As X-Band synthetic aperture radar (SAR) penetrates the snow and ice pack by several meters a new concept for absolute height adjustment was set up that relies on areas with stable penetration conditions and on ICESat (Ice, Cloud, and land Elevation Satellite) elevations. After DEM generation and editing, a sophisticated height error characterization of the whole Antarctic continent with ICESat and IceBridge data was carried out and a validation over blue ice achieved a mean vertical height error of just -0.3 m ± 2.5 m standard deviation. The filled and edited Antarctic TanDEM-X PolarDEM 90 m is outstanding due to its accuracy, homogeneity and coverage completeness. It is freely available for scientific purposes and provides a high-resolution dataset as basis for polar research, such as ice velocity, mass balance estimation or ortho-rectification.